Going Remote: Evaluating a Global Health Practicum Program During COVID-19 Travel Restrictions. Issue 1 (17th October 2022) - Harrison, Meagan; Chung, Eumihn; Kajungu, Dan; Mahapatra, Tanmay; Rahman, Mahbubur; Ungureanu, Marius-Ionut; Kalbarczyk, Anna
Background: Short-term experiences in global health (STEGHs) are an important part of global health degree programs. Due to the COVID-19 pandemic, travel was not possible for students planning to participate in the Johns Hopkins Center for Global Health's Global Health Established Field Placement (GHEFP) program in 2020. Working with willing faculty mentors, in-country collaborators, and students, the Center allowed students to complete their practicums remotely so that students could gain practicum experience despite not being able to travel, and faculty and collaborators could receive the planned support on their projects. Objectives: This evaluation aims to describe the experience of pivoting the GHEFP program from an in-person, in-country program to a remote practicum. Methods: We analyzed program evaluation data from 30 students, 20 faculty members, and 10 in-country collaborators. Surveys for each group consisted of multiple choice, scale rating, and open-ended questions. The quantitative data was analyzed using Microsoft Excel to calculate survey response frequencies. The open-ended responses were analyzed for emergent themes. Findings: The remote GHEFP experience enabled students to gain practice working on global health projects from a distance, but it came with challenges related to preparation, communication, shifting scopes of work, and contextualization. All participants would have preferred an in-person experience if given a choice, but most agreed that a remote practicum was better than not participating at all. Conclusions: The remote program served its purpose during the height of the pandemic. Given the hybrid nature of global health today, many aspects of the remote practicum experience are helpful for global health training. Future iterations of remote STEGHs should initially be designed for remote work to ensure meaningful scopes for students that are helpful to faculty mentors and collaborators. Hybrid models may also be useful. Mutually beneficial twinning relationships should also be incorporated into remote and in-person STEGHs to foster a more equitable global health training environment.